Strengthening evidence-based policymaking through WEFE modeling - Getaneh, Yonas; Balcha, Yodit; Abera, Wuletawu (2024)
Through the CGIAR Initiative on NEXUS Gains, the Alliance of Bioversity International and CIAT has been implementing the development of Water-Energy-Food and Ecosystem (WEFE) nexus analysis modeling tools using the FABLE Calculator (Food, Agriculture, Biodiversity, Land use and Energy) at the national scale. To this end, an inter-institutional Technical Working Group (TWG)—composed of sectoral ministries and government institutions working in the areas of food and land-use systems (food, climate mitigation, biodiversity, livestock, energy, fertilizer use, water, and macroeconomy)—was created to co-develop WEFE national pathways and targets, as well as conduct capacity-building training to enable/ training relevant stakeholders on the use of nexus tools for policy coherence. This report highlights the process and insights from the latest in a series of three TWG workshops, showcasing the refinement of development pathways and the introduction of an accessible Dashboard to support evidence-based policymaking through improved understanding of synergies, trade-offs, and sectoral priorities.